Retinoic and ascorbic acids induce osteoblast differentiation from human dental pulp mesenchymal stem cells (2021)
Previous studies have suggested an important role of retinoic acid (RA) and ascorbic acid (AA) in the stimulationof osteoblastic differentiation; however, the function of RA and AA in the osteogenic differentiation from humandental pulp (hDPSCs) remains unclear.Objective:Thisin vitrostudy investigated the effects of RA and AA on the differentiation of osteoblast fromhDPSCs.Methods:hDPSCs were treated with different doses of RA and AA, separately or in combination (RAþAA).Morphology and cell proliferation were assessed. Osteoblast differentiation was evaluated by alizarin red, alkalinephosphatase staining, andRUNX2gene expression.Results:A significant reduction was observed in the number of cells treated with RA (26%) and RAþAA (30%)after 12 days of treatment. AA treatment alone induced a 12% reduction in the number of cells. Morphologically,the cells treated with RA and RAþAA were larger and more elongated than the control cells. A mesh pattern wasobserved in cells treated with AA. Numerous calcified nodules were present in cells treated with RA, AA, and RAþAA. This coincided with increased expression ofRUNX2and high alkaline phosphatase staining levels.Conclusions:hDPSCs treated with RA and RAþAA showed significant reduction in proliferation, detectablemorphological changes, and expression of the key differentiation geneRUNX2, consistent with an osteoblastphenotype. AA induced morphological changes and early formation of calcified nodules. RA had a predominanteffect when AA and RA were used together.